Gamification is Working, but Which One Exactly? Results from an Experiment with Four Game Design Elements. Issue 3 (7th February 2023) - Mazarakis, Athanasios; Bräuer, Paula
Abstract: Current gamification research usually examines several game design elements at the same time, which makes it difficult to distinguish how and to what extent individual game design elements increase motivation. We address this research question by individually examining four game design elements (progress bar, narrative, feedback, and badges) in an online experiment. In addition, combinations of game design elements were tested to gain insight about additive effects on motivation. The study included 505 subjects who answered a maximum of 190 different multiple-choice questions. The subjects were told to answer questions only as long as they enjoyed answering them. The results provide statistically significant motivational gains for all individual game design elements. Interestingly, not all game design elements benefit from a combination in the same way. The results of our study indicate that an increase in motivation through gamification is already possible if only an individual game design element is added.